2013
DOI: 10.1007/978-3-642-39191-0_63
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Factors Involved in the Ability to Manipulate a Digital Camera

Abstract: The purpose of this study is to understand who user' property affects the ability to manipulate a digital camera. The N-back task, the action control scale, usability test, structural test, functional test, protocol analysis and some questioner are used to understand user' distinction. The relationships among each property and performance were cleared by correlation analysis. As a result, functional models about the camera are most important to use well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…This finding is consistent with the results of previous studies on mental models in usability and cognitive engineering fields. Previous studies [19,20,22] reported that operation performance improved when users construct appropriate mental models and that the usability of products for which mental models are easy to construct is good. In other words, to improve the usability of a product and increase the user's operating performance, it is important that the user is able to construct a mental model that fits the system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding is consistent with the results of previous studies on mental models in usability and cognitive engineering fields. Previous studies [19,20,22] reported that operation performance improved when users construct appropriate mental models and that the usability of products for which mental models are easy to construct is good. In other words, to improve the usability of a product and increase the user's operating performance, it is important that the user is able to construct a mental model that fits the system.…”
Section: Discussionmentioning
confidence: 99%
“…The structural model relates to the comprehension of a structure and a working principle to assume "how a device works?". Mental model tests from the perspective of functional and structural models have been used in previous studies and found to be valid [21][22][23]. Therefore, the author adopted these tests to measure the level of mental model construction.…”
Section: Task 221 Digital Camera Operationmentioning
confidence: 99%
See 2 more Smart Citations